Practical use of hydrogen as a strategic energy carrier on the example of the railway sector - Beroud Alan (Przegląd Komunikacyjny)
Abstract: In the article, the author submits and analyzes the assumptions of the EU climate and energy policy. He also indicates and describes the condition and prospects of the Polish energy sector in the context of the use of new energy sources. The publication includes - supported by calculations - arguments for the use of hydrogen as a strategic energy source on the example of the railway sector.